Effects of Fatty-Type and Lean-Type on Growth Performance and Lipid Droplet Metabolism in Pekin Ducks - Zhong Zhuang; Tingshuo Yang; Wenqian Jia; Meng Bai; Hao Bai; Zhixiu Wang; Guohong Chen; Yong Jiang; Guobin Chang (Animals, 2022)
The reasons for differences in lipid depositions between fatty-type (F-T) and lean-type (L-T) ducks remain unknown. The present study aimed to compare the growth performance, lipid deposition, and gene expression related to lipid droplet formation in F-T and L-T Pekin ducks. One-day-old, 140 each L-T and F-T male ducks were selected and distributed separately into 20 replicate cages. All ducks were fed commercial diets up to 35 d of age. F-T ducks had a higher average daily gain from 21 to 28 d of age. On 35-day-old, F-T ducks had higher serum levels of high- and low-density lipoprotein cholesterol, cholesterol, albumin, and hydroxybutyrate dehydrogenase activity than L-T ducks. F-T ducks had higher abdominal fat and subcutaneous fat percentages than those in L-T ducks. Liver histological examination showed that L-T ducks contained more lipid droplets in the liver, which gradually decreased with increasing age. The average adipocyte area and diameter of abdominal fat and subcutaneous fat in the F-T and L-T ducks increased with age and were higher in F-T ducks than those in L-T ducks. Furthermore, the gene expression of perilipin 1, perilipin 2, angiopoietin-like protein 4, adipose triglyceride lipase, alpha/beta-hydrolase domain-containing protein 5 (ABHD5), and serine/threonine kinase 17a in the liver, abdominal fat, and subcutaneous fat of F-T ducks was higher than that in L-T ducks, and it increased with age. Compared to L-T ducks, F-T ducks had higher expression of ABHD5 in the abdominal fat and subcutaneous fat and lower expression in the liver. Thus, F-T ducks displayed lower hepatic lipid deposition and a higher percentage of abdominal fat and subcutaneous fat, suggesting that F-T ducks had higher lipid storage capacity due to increased gene expression related to lipid droplets.